General model for analyzing data on the rate of reactive dissolution of poly-disperse particulate solids - Bhattacharya, Arijit (Chemical Engineering Journal, 2008)
A model has been presented which successfully simulates the experimentally observed integral batch reactive dissolution rate data while accounting for the poly-dispersity of the solid particulate charge. This allowed avoiding arbitrary assumptions about the particulate inventory and size independence of the mass transfer coefficient. There is also no need for a priori identification of the controlling regime, which can change from kinetic to mass transfer during the process, apart from the possibility of the shift with the specified process and operating conditions. The model was applied with equal ease to a simple isothermal reaction, an exothermic reaction with runaway potential and to a phase-transfer catalysis reaction with a complex mechanism. The model was shown to predict the time required for a specified extent of conversion of the particulate reactant or the rate of consumption of a key liquid reactant under a variety of process and operating conditions, like temperature, liquid reactant and the catalyst concentration, particle size, poly-dispersity of the charge and agitation speed. Such information is useful in reactor design and scale-up. Where dissolution is accompanied with a runaway reaction, the model can predict quantities of interest in hazard assessment and should aid safe reactor design. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: kinetic model; particle size distribution; poly-disperse solid reactant; reactive dissolution; reactive thermal hazard; solid-liquid PTC reaction